Multidisciplinary sequential diagnosis and treatment for mouth breathing in children - LI Yuanyuan, LIU Yuehua (Editorial Office of Stomatology, 2024)
Mouth breathing in children not only affects the growth and development of teeth and maxillofacial, but also may seriously affect the physical and mental health of children with sleep disordered breathing. Mouth breathing can be divided into obstructive mouth breathing and habitual mouth breathing. Its occurrence and development may be related to various systemic diseases such as allergy, inflammation, immunity, genetics, etc. It also involves changes in the structure of the oral temporomandibular joint, perioral muscle group, dental arch morphology, and development of the upper and lower jaws. Therefore, the treatment of mouth breathing in children should be a multidisciplinary combined sequential treatment plan based on the causes associated with different organs or systems. From the perspective of orthodontists, this paper analyzes the diagnosis and treatment process of different types of mouth breathing, so as to provide reference for clinicians.